Effect of age and sex on skin thickness and body temperature of Damascus goats in Aljabal Alakhdar region (Libya) - Amaizik, S; El-Jarari, I; Belgasem, M.; Milad, I. (Al-Mukhtar Journal of Sciences, 2007)
An experiment was carried out on 24 Damascus goats (11 males and 13 females) to investigate the effect of age and sex on some physiological traits in summer. Body weight was taken and selected physiological parameters were measured such as: body temperature, hair, skin temperatures and skin thickness of neck and flank. Heat tolerance was calculated. Results obtained indicated that no significant differences between males and females in all studied traits except the overall mean of body weight which was significantly higher (P < 0.05) in males compared to females. The age was significantly affect (P < 0.01) all studied characteristics except skin temperature in flank. Body temperature¸ hair and skin temperatures of neck and flank were decreased with advanced age and reach to the lowest values (P < 0.01) in age 1.5 years compared to other ages. On the opposite direction¸ heat tolerance and skin thickness of neck and flank were increased significantly (P < 0.01) with advanced ages. Meanwhile, the interaction between sex and age were significant in some traits such as: body weight (P < 0.01) , hair temperatures of neck and flank (P < 0.05) and skin thickness of neck and flank. It was concluded from this study that age was more affect selected physiological parameters than sex of Damascus goats under hot climates conditions. However, further research is needed under cold weather.